An enantioselective synthesis of β2-amino acid derivatives - Elaridi, Jomana (2005)
Enantioselective hydrogenation of a series of (E)-α-substituted β-amidoacrylates using Rh(I)-catalysts with chiral phosphine ligands (BPE, DuPHOS) gives β2-amino acid derivatives with enantioselectivities of up to 67%. A β2,3-amino acid derivative was also synthesised with similar enantioselectivity (⩽65%) from the corresponding prochiral enamide.